2020
DOI: 10.1128/aac.00760-20
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of the Optimal Dose of Meropenem in Critically Ill Infants and Children: a Developmental Pharmacokinetic-Pharmacodynamic Analysis

Abstract: Data of developmental pharmacokinetics (PK) of meropenem in critically ill infants and children with severe infections are limited. We assessed the population PK and defined the appropriate regimen to optimize treatment in this population based on developmental PK-pharmacodynamic (PD) analysis. Blood samples were collected from pediatric intensive care unit patients with severe infection treated with standard dosage regimens for meropenem. Population PK data were analyzed using NONMEM software. Fifty-seven pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…Another very recent study included 57 patients in the PICU, 35 with sepsis, with a median age of 1.44 years (range 0.101-14.4 years) and CL CR estimated by the Schwartz formula of 155 mL/min/1.73 m 2 (57.9-279 mL/min/1.73 m 2 ). 82 Most patients (43 of 57) had an eCL CR ≥ 130 mL/min/1.73 m 2 . The eCL CR was included as a covariate on total meropenem clearance using an empirical power function.…”
Section: Complexities Associated With Antibiotic Therapy In Patients mentioning
confidence: 93%
See 1 more Smart Citation
“…Another very recent study included 57 patients in the PICU, 35 with sepsis, with a median age of 1.44 years (range 0.101-14.4 years) and CL CR estimated by the Schwartz formula of 155 mL/min/1.73 m 2 (57.9-279 mL/min/1.73 m 2 ). 82 Most patients (43 of 57) had an eCL CR ≥ 130 mL/min/1.73 m 2 . The eCL CR was included as a covariate on total meropenem clearance using an empirical power function.…”
Section: Complexities Associated With Antibiotic Therapy In Patients mentioning
confidence: 93%
“…Simulations suggested 80% of patients in the PICU with ARC did not achieve therapeutic meropenem exposure for susceptible pathogens. Another very recent study included 57 patients in the PICU, 35 with sepsis, with a median age of 1.44 years (range 0.101–14.4 years) and CL CR estimated by the Schwartz formula of 155 mL/min/1.73 m 2 (57.9–279 mL/min/1.73 m 2 ) 82 . Most patients (43 of 57) had an eCL CR ≥ 130 mL/min/1.73 m 2 .…”
Section: Complexities Associated With Antibiotic Therapy In Patients mentioning
confidence: 99%
“…But Shekar et al found that variability in meropenem clearance was correlated with creatinine clearance or the presence of CRRT ( Shekar et al, 2014 ). Wang et al demonstrated that standard dosage regimens for meropenem did not meet an appropriate PD target but they did not do research on children undergoing extracorporeal life support (ECLS) ( Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…At a MIC of 8 mg/L, the CI of MER (90 mg/kg/d) might achieve an optimal PTA in children with creatinine clearances of 40–120 mL/min/1.73 m 2 . In addition, Wang et al [ 25 ] found that the PTA values for pathogens with high MICs (4 and 8 mg/L), such as Enterobacteriaceae and Pseudomonas aeruginosa , could still reach 98.0% and 73.3%, respectively, in severely infected infants and children after CI of MER (110 mg/kg/d). Germovsek et al [ 26 ] performed simulations based on a PPK model in neonates and infants with severe infections and stated that the EI/CI modes could increase the plasma PTA but might decrease the PTA in cerebrospinal fluid.…”
Section: Resultsmentioning
confidence: 99%